(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This study investigates the pronunciation of German monophthongs (L3) by Malay speakers. It also compares the way the L3 monophthongs are produced with the monophthongs produced in Standard Malay (L1) and English (L2) to examine if there are any similarities in the way that equivalent vowels are produced. A total of 10 female Malay speakers who were learning German were recorded reading aloud carrier sentences containing the target vowels in a /bVd/ and a /bVt/ context in all three languages. All these speakers also speak English as a second language. Based on the formant frequency model, the first (L1) and second (L2) formants of the target monophthongs were measured. The duration of the vowels was also measured. Scatter plots of the vowels were also generated to enable comparison among similar sets of vowels within and among the three languages within the context of L3 acquisition. The findings suggest that speakers tend to produce equivalent vowels with similar acoustic properties, whilst tending to collapse "new" ones in the L3 to neighbouring L1 or L2 vowels. The findings from this study contribute to the growing area of L3 acquisition research. Keywords: monophthong, L3 acquisition, German, Malay, English